On zeros of functions of given proximate formal order analytic in a half-plane
We describe sequences of zeros of functionsf≢0 that are analytic in the half-plane ℂ+=z:Rez> and satisfy the condition ε > 0c_1 (0; + ∞ )z C_ + :| f(z) | c_1 ( (σ + ε )| z |η (| z |) ) where 0≤σ, number=7, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Vynnyts’kyi, B. V. and Sharan, V.L., year=1999, month=Jul., pages=904–909